2019
DOI: 10.29337/ijops.26
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Sural Artery Perforator Island Flap as a Simpler Alternative for Prophylactic Skin Augmentation Prior to Total Knee Arthroplasty

Abstract: Surgical Anatomy At the very least, the medial sural artery perforator [MSAP] flap will capture the skin territory overlying the medial gastrocnemius muscle. The medial sural artery is the source vessel to that muscle as it is to this flap; and is a branch of the popliteal artery, originating at or about the knee joint [4]. After entering the undersurface of the muscle, most commonly the medial sural artery bifurcates to run superficial [posterior] or deep within the muscle surface [5]. Although the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, any patient with tenuous soft tissues in the knee region, including the presence of a skin graft or multiple preexisting scars, should be considered at risk for eventual wound breakdown and be a candidate for prophylactic soft-tissue augmentation preceding or at the same time as the arthroplasty. 1,2,4,5 Casey et al corroborate this opinion as they showed that in such situations disastrous skin-healing complications after TKA virtually never occurred if some form of prophylactic flap were used in advance. 2 They accomplished this using the medial gastrocnemius muscle as a local flap, or with a free flap using both muscle and perforator flaps for larger defects.…”
mentioning
confidence: 91%
“…Thus, any patient with tenuous soft tissues in the knee region, including the presence of a skin graft or multiple preexisting scars, should be considered at risk for eventual wound breakdown and be a candidate for prophylactic soft-tissue augmentation preceding or at the same time as the arthroplasty. 1,2,4,5 Casey et al corroborate this opinion as they showed that in such situations disastrous skin-healing complications after TKA virtually never occurred if some form of prophylactic flap were used in advance. 2 They accomplished this using the medial gastrocnemius muscle as a local flap, or with a free flap using both muscle and perforator flaps for larger defects.…”
mentioning
confidence: 91%
“…The results of flap success in other studies were: Kao et al [10] had one failed case from 29 patients, Agrawal et al [14] worked on 10 patients with one failed case, Toyserkani et al [8] had worked on 10 patients with 6 uncomplicated cases, 2 total flap losses due to venous congestion, one case had a venous problem that was salvaged and one the flap was changed intraoperative, Chen et al [9] worked on 11 patients with one flap failed, Shun et al [15,16] worked on 31 patients with one flap failed due to pressure on the pedicle and Balan et al [13] worked on seven patients with one flap has a partial loss.…”
Section: Discussionmentioning
confidence: 99%
“…24,75,82 Prophylactic para-patellar soft-tissue augmentation especially for secondary knee surgery such as a repeat total knee prosthesis can prevent later untoward wound healing issues leading to loss of the prosthesis. 104,105 The popliteal space such as following a knee scar flexion contracture can also be resurfaced with a pedicled MSAP flap to avoid a skin graft that might recontract. 67 V-Y advancement island flaps requiring minimal perforator intramuscular dissection can reach other adjacent calf defects.…”
Section: Legmentioning
confidence: 99%
“… 24 75 82 Prophylactic para-patellar soft-tissue augmentation especially for secondary knee surgery such as a repeat total knee prosthesis can prevent later untoward wound healing issues leading to loss of the prosthesis. 104 105 …”
Section: The Versatilitymentioning
confidence: 99%